2010
DOI: 10.1590/s1413-70542010000400013
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho agronômico de linhas endogâmicas ecombinadas de Capsicum annuum L. em sistema orgânico sob cultivo protegido

Abstract: RESUMOO manejo de plantas em cultivo protegido e a busca de produtos orgânicos pelos consumidores têm sido um desafio para produtores e pesquisadores de hortaliças. Para que essas formas de cultivo proporcionem lucratividade ao produtor e frutos de qualidade para o consumidor, faz-se necessária a busca por genótipos adaptados a esse manejo diferenciado. Neste trabalho, objetivouse avaliar o desempenho de 12 linhas endogâmicas recombinadas de Capsicum annuum L., obtidas do cruzamento entre os acessos UENF 1421 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
1
7
0
1
Order By: Relevance
“…Campos dos Goytacazes, UENF, 2014. testing is allowed as it ensures the consistency of results with the proper use of evaluation methods (Lovato, 2011). Recombinant lines come from the same two-parent cross and there is a need for morphological trait analysis that would allow for differentiation among them, beyond agronomic characteristics used during the final stages of selection of such lines in the breeding program, as performed by Moreira et al (2009Moreira et al ( , 2010. The descriptors used in the DUS tests have enabled to distinguish lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Campos dos Goytacazes, UENF, 2014. testing is allowed as it ensures the consistency of results with the proper use of evaluation methods (Lovato, 2011). Recombinant lines come from the same two-parent cross and there is a need for morphological trait analysis that would allow for differentiation among them, beyond agronomic characteristics used during the final stages of selection of such lines in the breeding program, as performed by Moreira et al (2009Moreira et al ( , 2010. The descriptors used in the DUS tests have enabled to distinguish lines.…”
Section: Resultsmentioning
confidence: 99%
“…The second is the source of disease resistance, whose genetic control is due to three recessive genes (Riva et al, 2004). After generations of inbreeding via SSD, the recombinant lines were selected for bacterial spot resistance and other attributes (Moreira et al, 2009(Moreira et al, , 2010.…”
Section: Resumo Proteção De Cultivares De Hortaliças No Brasil: Um Esmentioning
confidence: 99%
“…This correlation, evaluated with repetition, was 61% (r = 0.61, P<0.0001, 1000 simulations), considering an appropriate value, with a good fit between the graphical representation of the genetic similarity and the matrix of similarity. Moreira et al (2010) found CCC (r) of 0.92, evaluating J. curcas. According to Vaz Patto et al (2004), values of r>0.56 are considered ideal, denoting consistence with the genetic similarity values.…”
Section: Resultsmentioning
confidence: 98%
“…Despite the lack of basic technical information, J. curcas crops are being disseminated and implemented in several regions of Brazil (NERY et al, 2013), however, the number of J. curcas accessions introduced in Brazil is low, leading to the occurrence of related accessions from different regions of the country, indicating a low genetic divergence for this species (ROSADO et al, 2010;BORGES et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Monteiro et al (2010) constataram coeficiente de variação de 8,9% para largura de fruto. Moreira et al (2010) apresentaram o coeficiente da variação para produção de 23%; para diâmetro de fruto, o coeficiente de variação foi de 17,04%. Sousa & Maluf (2003) registraram um coeficiente de variação de 45,54% para produção total de fruto de pimenta; para comprimento de fruto e diâmetro de fruto, o coeficiente de variação foi …”
Section: Resultsunclassified